Impact of brand equity on purchase intentions: empirical evidence from the health takāful industry of the United Arab Emirates. Issue 3 (19th May 2021) - Rizwan, Shahid; Al-Malkawi, Husam-Aldin; Gadar, Kamisan; Sentosa, Ilham; Abdullah, Naziruddin
Abstract : Purpose: Although 76% of the population of the United Arab Emirates (UAE) is Muslim, takāful (Islamic insurance) has a much smaller share of business in the UAE than conventional insurance does. The purpose of this study is to highlight the importance of brand equity (BE), which is known as the incremental value that provides reason to buy a brand. This study provides useful insights that can help the health takāful industry to gain a feasible market share in the UAE. Design/methodology/approach: This is a quantitative study in which stratified random sampling was adopted for data collection from 300 respondents through a self-administered questionnaire from August to November 2018. Underpinning the study is the theory of planned behavior (TPB) and the structural equation modeling (SEM) technique has been used to examine the impact of BE on purchase intentions (PI) through the moderating role of demographic factors such as age, income, education and religion. Three dimensions of BE, i.e. brand awareness (BAW), brand association (BAS) and perceived quality (PQ), are evaluated in terms of their significance as dimensions of BE. Findings: The major findings of this study confirm that BE has a strong positive influence on the PIs of health takāful customers in the UAE and that all three dimensions of BE make significant contributions to the overall BE. The results show that education does moderate the relationship between BE and PI while age, income and religion do not. A new finding of this study is the nonsignificant moderating role of religion, whereby it was found that takāful products in the UAE are not limited to Muslim customers but can include potential customers who are followers of other religions. Originality/value: To the best of our knowledge, the present study is the first of its kind to examine the impact of BE on the PI of health takāful customers in the UAE. The findings of the study give academia, researchers and marketers a better understanding of the importance of BE and of its vital role in promoting takāful products in the Gulf Cooperation Council (GCC) countries such as the UAE.